Beneath The Horror of Human Trafficking in Laos: Unraveling Asean's Efforts and Failures Through the Lens Of Neoliberal Institutionalism - Kartika, Anindya Sekar; Kamila Hermawan, Ammara; Nicodemus Bourney Purba, Jeremy; Faria Faculto de Jesus, Luizinha (Jurnal Multidisiplin Indonesia, 2023)
This study aims to examine the role of ASEAN, with a specific focus on the Indonesian Chairmanship in 2023 and the future Lao chairmanship in 2024, in addressing the persistent issue of non-traditional security concerns, specifically human trafficking and sex trafficking, which have been prevalent in Laos for an extended period of time. In addition, this analysis will explore the involvement of Lao governments and residents in order to gain a comprehensive understanding of the underlying factors contributing to the enduring prevalence of human trafficking in Laos or arenas such as GTSEZs which has exploited Laotian workers. This study will employ a qualitative research methodology, employing the theoretical framework of neoliberal institutionalism to examine the extent to which ASEAN has achieved success or failure in fostering cooperation as an institution. In addition, this study will thoroughly examine the intricacies of domestic politics in Lao. This study reveals that ASEAN has undertaken many initiatives, including ACTIP, NRM, and collaboration between Indonesia and Laos. However, upon further analysis of the government of Lao's endeavors in resolving this subject, it becomes evident that their attempts have been inadequate in terms of institutional capacity, domestic political considerations, and cultural comprehension. Hence, in order to enhance the efficacy of ASEAN's endeavors, it is imperative for the Lao government to demonstrate unwavering dedication in addressing the horror of human trafficking.